“Bumps in the Road”: A Pilot Study of a Therapeutic Technique for the Integration of Unresolved Family Loss and Trauma - Watts, Gabriella J.; Lewis, Andrew J.; Serfaty, Irene G. (Frontiers in Psychology, 2021)
The ability to sustain a coherent narrative about experiences of trauma and loss is a prominent feature of secure-autonomous attachment states of mind as assessed in narrative tasks such as the Adult Attachment Interview. The current study examines the clinical application of the concepts of narrative coherence and discourse segregation within a therapeutic intervention for whole families. Bumps in the Road is a family drawing task, which aims to facilitate the co-construction of family narratives about adversities such as trauma, loss and hardship. The technique aims to increase the family’s narrative coherence about such challenging events. The paper first presents a description of the task itself together with the discourse theories of defensive processing of adverse events. The study also presents pilot quantitative findings from 19 parents on the psychometric properties of a coding system of the families’ discourses in undertaking the task and the therapist’s techniques in administering the task. The predictive association of coding of the narratives were examined as predictors of change in internalising and externalising symptoms in the referred child, using the Child Behaviour Checklist. Findings showed that therapist competence in administration of the task did significantly predict the magnitude of treatment efficacy. The current study is the first presentation of this novel therapeutic task and sets a platform for further research on the use of narrative tasks and the formal coding of discourse in therapeutic work with children and families.